Atrial High-Rate Episodes in Elderly Patients: The Anticoagulation Therapy Dilemma - Pimpini, Lorenzo; Biscetti, Leonardo; Matacchione, Giulia; Giammarchi, Cinzia; Barbieri, Michelangela; Antonicelli, Roberto (Journal of clinical medicine, 2024)
Atrial fibrillation (AF) has been associated with higher morbidity and mortality rates, especially in older patients. Subclinical atrial fibrillation (SCAF) is defined as the presence of atrial high-rate episodes (AHREs) > 190 bpm for 10 consecutive beats > 6 min and <24 h, as detected by cardiac implanted electronic devices (CIEDs). The selection of eligible patients for anticoagulation therapy among elderly individuals with AHREs detected through CIEDs remains a contentious issue. The meta-analysis of ARTESiA and NOAH-AFNET 6 clinical trials revealed that taking Edoxaban or Apixaban as oral anticoagulation therapy can reduce the risk of stroke by approximately 32% while increasing the risk of major bleeding by approximately 62%. However, it is still unclear which are, among patients with SCAF, those who can take the highest net clinical benefit from anticoagulant therapy. The present review summarizes the current evidence on this intriguing issue and suggests strategies to try to better stratify the risk of stroke and systemic embolism in patients with AHREs. We propose incorporating some parameters including chronic kidney disease (CKD), obesity, enlarged left atrial volume, the efficacy in blood pressure management, and frailty into the traditional CHA2DS2-VASc score. Future trials will be needed to verify the clinical usefulness of the proposed prognostic score mainly in the view of a personalized therapeutic approach in patients with SCAF.